Pengaruh Ukuran Partikel dan Lama Maserasi terhadap Karakteristik Ekstrak Virgin Coconut Oil Wortel (Daucus carota L.) sebagai Pewarna Alami - Ardyanti, Ni Komang Novy Trisna; Suhendra, Lutfi; Ganda Puta, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): SeptemberDO - 10.24843/JRMA.2020.v08.i03.p11, 2020)
Carrots are vegetable plants that contain ?-carotene, carotenoids, and vitamin A which can be extracted with organic (non-polar) solvents. Virgin Coconut Oil (VCO) is a non-polar solute suitable for dissolving natural dyes and has a dielectric constant of 2.82 × 10 -18 , so that VCO can be used as a solvent in carotenoid extraction in carrots. The purpose of this study were to determine the effect of particle size and maceration duration on the characteristics of carrot VCO extract as a natural dye and obtain the best particle size and maceration time to obtain carrot VCO extract as a natural dye. This experiment was designed using a Randomized Block Design with two factors. The first factor is the particle size which consists of 3 levels, namely: P1 (40 mesh), P2 (60 mesh), and P3 (80 mesh). The second factor is maceration time which consists of 3 levels, namely: W1 (4 hours), W2 (6 hours), and W3 (8 hours). Data were analyzed by analysis of variance and continued with Tukey test. The results showed that particle size and maceration time a very significant effect on yield, total carotenoids, total ?-carotene levels, brightness level (L*), redness level (a*) and yellowish level (b*). Treatment particle size 80 mesh and maceration duration of 6 hours was the best treatment to extract carrot VCO with yield characteristics of 0.77 percent, total carotenoids 2425.9 (mg/L), total ?-carotene levels 123.39 (mg/L), brightness level (L *) 34.77, redness level (a *) 14.67, and yellowish level (b *) 25.84. Keywords : VCO, carrot, extraction, particle size, time maceration.